Biomarker-guided management of acute kidney injury. Issue 6 (December 2020) - Kane-Gill, Sandra L.; Meersch, Melanie; Bell, Max
Abstract : Purpose of review: The current narrative review discusses practical applications of stress and damage biomarkers for the management of acute kidney injury (AKI) based on clinical trials and real-world evaluations. Recent findings: In 2013 with the discovery and validation study of biomarkers for AKI (Sapphire) advancement in care was provided allowing for the early identification of patients at high risk for developing AKI. It was the combination of new biomarkers and the Kidney Disease Improving Global Outcomes (KDIGO) guidelines for managing patients with AKI that provided an opportunity to improve patient care. In 2017, the PrevAKI study implemented KDIGO guideline management in high-risk patients identified by biomarkers followed in 2018 with the BigPAK study that used a similar approach, both of which demonstrated positive outcomes in patient care. Next, real-world evaluations followed supporting biomarker guided management of AKI in clinical practice. Also, proposals for better nephrotoxin management, a major modifiable exposure to prevent AKI, were provided with the foresight in identifying high-risk patients. Summary: Stress and damage biomarker-based approaches to patient care seem to be promising for identifying patients at high risk for developing AKI and thus offers an opportunity for early management to prevent and ameliorate AKI and drug-associated AKI.